(untitled) (Asian Journal of Agriculture, 2023)
Abstract. Sagitarian DGF, Astikasari L, Rahmayani D, Armando MF, Nugroho GD, Himawan W, Mutaqin AZ, Md. Naim D, Setyawan AD. 2023. Biodiversity of edible fruit sold at Pasar Gede, Surakarta City, Central Java, Indonesia. Asian J Agric 7: 57-68. The market is a place to purchase numerous varieties of goods. Pasar Gede is a traditional Indonesian marketplace in Surakarta City, Central Java, Indonesia. It is the earliest and the largest fruit market in Surakarta. This study was conducted to ascertain the variety species of fruits sold at Pasar Gede from 12 to 16 December 2022. Direct interviews with Pasar Gede administrators and sellers conducted the sampling. This study uses primary data from interviews and secondary data from literature studies to support the primary data, while descriptive analysis was performed on the collected data. The results revealed that the fruit sold at Pasar Gede comprised 82 species from 25 families, with information on local name, price, seasonality, rarity according to vendors, and conservation status according to the IUCN Red List. In Pasar Gede, fruits with conservation status Least Concern (LC) based on the IUCN Red List were found, namely juwet (Syzygium cumini (L.) Skeels), matoa (Pometia pinnata J.R.Forst. & G.Forst.), jambu biji (Psidium guajava L.), pir packham (Pyrus communis L.), srikaya (Annona squamosa L.), jeruk bali (Citrus maxima (Burm.) Merr.), delima arab (Punica granatum L.), sirsak (Annona muricata L.), sawo (Manilkara zapota (L.) P.Royen), asam jawa (Tamarindus indica L.) and kesemek (Diospyros kaki L.f.). Jeruk (Citrus sp.), apel/pir (Pyrus sp.), pisang (Musa sp.), mangga (Mangifera sp.), and alpukat (Persea sp.) are the dominant fruits (the most available and frequently sold by every vendor in his stall) in Pasar Gede. Anggur autum (Vitis vinifera L. cv. autumn) are the most expensive products at 180,000 IDR per kilogram, while jambu biji is the least expensive at 8,000 IDR per kilogram. The production cost, seasonality, and fruit quality determine whether fruit prices are costly. The abundance of fruit indicates that Pasar Gede is a comprehensive fruit market center in Indonesia, particularly in Surakarta.